Academic Fraud dan Karakter Bela Negara pada Mahasiswa Akuntansi: Sebuah Analisis Bibliometrik (2021–2025) - Rahma Dwi Fitriana; Indrawati Yuhertiana (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2026)
Academic fraud has become a pressing issue in higher education, particularly in accounting programs that demand high integrity. Previous studies have largely focused on descriptive or quantitative approaches, leaving a gap in mapping the thematic landscape and its linkage to national defense values. This study aims to analyze the phenomenon of academic fraud and its relationship with the formation of national defense character in accounting students, while addressing the research gap by identifying dominant themes and their ethical implications. Data were obtained from 17 articles published on Google Scholar between 2021–2025. Bibliometric analysis was conducted using VOSviewer 1.6.20, employing four metrics: citations, co-citations, bibliographic couplings, and keyword co-occurrences. The mapping revealed six thematic clusters: (1) academic dishonesty and fraud, (2) determining factors such as corruption, pressure, and rationalization, (3) manifestations of fraudulent behavior in higher education, (4) critical discourse and methodological issues, (5) theoretical and ethical foundations, and (6) links to national defense. The most significant finding is that academic pressure and rationalization emerge as dominant drivers, while integrating national defense values provides a normative framework to strengthen ethical awareness among accounting students. These findings confirm that academic fraud is not only an educational problem but also a moral and national issue. Practically, the study implies the need for universities to integrate ethics and national defense education into curricula, design proportional academic policies, and foster a culture of integrity. Theoretically, the study bridges bibliometric mapping with national defense discourse, offering a novel perspective rarely explored in the literature.